1997
DOI: 10.1002/(sici)1096-9071(199703)51:3<152::aid-jmv3>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Use of polymerase chain reaction to provide prognostic information on human cytomegalovirus disease after liver transplantation

Abstract: Sixty-four consecutive liver transplant patients receiving 76 organs have been monitored for human cytomegalovirus (HCMV) in blood and urine posttransplantation using a polymerase chain reaction (PCR) assay that amplifies a 149 base pair fragment of the glycoprotein B gene. Six hundred and twenty-six blood and 310 urine samples were analysed during surveillance. Thirty-two patients had CMV infection (50%), 12 of whim progressed to HCMV disease. Detection of HCMV in either blood or urine was significantly assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 24 publications
(24 reference statements)
0
18
0
1
Order By: Relevance
“…Allograft rejection, sepsis, acute illness, IL-6 and TNF have long been implicated in reactivation of HCMV in patients (Cook et al, 1998;Döcke et al, 1994;Fietze et al, 1994;Grattan et al, 1989;Heininger et al, 2001;Hibberd et al, 1992;Kalil & Florescu, 2009;Kutza et al, 1998;Lao et al, 1997;Limaye et al, 2008;Mutimer et al, 1997;Portela et al, 1995;Razonable et al, 2001;Reinke et al, 1994a) and allogeneic stimulation, TNF, IL-6 and lipopolysaccharide have been shown to induce reactivation of HCMV in experimental models (Hargett & Shenk, 2010;Huang et al, 2012;Kew et al, 2014;O'Connor & Murphy, 2012;Reeves & Compton, 2011;Söderberg-Nauclér et al, 1997). Allogeneic transplantation and TNF are sufficient to activate both an HCMV MIEP-lacZ transgene and MCMV IE gene expression (Hummel et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allograft rejection, sepsis, acute illness, IL-6 and TNF have long been implicated in reactivation of HCMV in patients (Cook et al, 1998;Döcke et al, 1994;Fietze et al, 1994;Grattan et al, 1989;Heininger et al, 2001;Hibberd et al, 1992;Kalil & Florescu, 2009;Kutza et al, 1998;Lao et al, 1997;Limaye et al, 2008;Mutimer et al, 1997;Portela et al, 1995;Razonable et al, 2001;Reinke et al, 1994a) and allogeneic stimulation, TNF, IL-6 and lipopolysaccharide have been shown to induce reactivation of HCMV in experimental models (Hargett & Shenk, 2010;Huang et al, 2012;Kew et al, 2014;O'Connor & Murphy, 2012;Reeves & Compton, 2011;Söderberg-Nauclér et al, 1997). Allogeneic transplantation and TNF are sufficient to activate both an HCMV MIEP-lacZ transgene and MCMV IE gene expression (Hummel et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a greater understanding of the molecular events controlling reactivation from latency is needed to develop alternative strategies to prevent CMV disease. Döcke et al, 1994;Fietze et al, 1994;Grattan et al, 1989;Heininger et al, 2001;Hibberd et al, 1992;Kalil & Florescu, 2009;Kutza et al, 1998;Lao et al, 1997;Limaye et al, 2008;Mutimer et al, 1997;Portela et al, 1995;Razonable et al, 2001;Reinke et al, 1994aReinke et al, , 1994b) and the inflammatory cytokine TNF has been proposed to drive reactivation through NF-k B-mediated activation of the major immediate early promoter (MIEP) (Döcke et al, 1994;Fietze et al, 1994;Prösch et al, 1995;Stein et al, 1993). However, due to the species specificity of HCMV, it has not been possible to test this hypothesis in the context of organ transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…CMV QNAT is the main alternative option to antigenemia (63)(64)(65)(66)(67)(68)(69). The testing requires expensive equipment and specialized expertise.…”
Section: Diagnosismentioning
confidence: 99%
“…The amount of DNA is extrapolated from a standard curve derived from the amplification of known amounts of the external standard. By using this method, significantly higher levels of CMV DNA were seen in liver transplant recipients with CMV disease than in asymptomatic CMV-infected allograft recipients (101,122,255,347). After treatment, clearance of CMV DNA with undetectable PCR signal has been associated with the disappearance of symptoms (101).…”
Section: Pcr Amplificationmentioning
confidence: 99%